Pengaruh Model Pembelajaran Make a Match Berbantuan Media Diorama Terhadap Hasil Belajar Peserta Didik Pada Materi Siklus Air Di Kelas V SDN 62 Banda Aceh - Ulfia, Ulfia; Safiah, Intan; Fitriani, Suci (Elementary Education Research, 2022)
This study entitled The Effect of Make A Match Learning Model Assisted by Diorama Media on Student Learning Outcomes on Water Cycle Material in Class V SDN 62 Banda Aceh. The formulation of the problem in this study is "is there a significant effect of the make a match learning model assisted by diorama media on student learning outcomes on the water cycle material in class V SDN 62 Banda Aceh?". This study aims to determine the effect of the make-a-match learning model assisted by diorama media on student learning outcomes on the water cycle material in class V SDN 62 Banda Aceh. The research uses a quantitative approach. This type of research is True Experimental with Posttest Only Control design. The research was conducted at SDN 62 Banda Aceh in Cot Mesjid Village. Sampling used the Random Sampling technique with a total of 62 students in class VA and VB. The data collection technique used a posttest test, while the data analysis technique used an independent t-test and SPSS Statistics 24. The results of hypothesis testing obtained a significance value (2-tailed) of 0.000 0.05. Then the decision criteria are H_a accepted and H_0 rejected. It can be concluded that there is a significant effect of using the Make A Match learning model assisted by Diorama media on student learning outcomes on the water cycle material in class V SDN 62 Banda Aceh